Migrasi dan Problematika Minoritas Muslim - Ahmad Maulidizen; Mamduh Tirmidzi; Habiburrahman Rizapoor (UIN K.H. Abdurrahman Wahid Pekalongan, 2021)
The issues surrounding Migration and the Problems of Muslim Minorities in the Modern World have become a hot topic of discussion and are constantly changing. This issue is fascinating, not only by Muslims but also by non-Muslims. The coverage of foreign (Western) media that always corners Islam (not individuals in Islam) and global terror events is very effective in changing a countryâ€™s policy to fight Islam. However, this does not mean that they (the West) are discriminatory actions against Muslims who live there. This study aims to review migration events and how the conditions of Muslim immigrants in Bali and several essential countries in Europe and Asia. This article is library research and empirical facts obtained from various current and reliable news sources. This event examines the extent of the fate of Muslim immigrants in multiple countries with different characters and critically examines how the policies of these countries impact Muslim minorities. In addition, a comparative study was also conducted on the condition of Muslim immigrants who became minorities in several countries with different backgrounds and characters. The results of this research are: First, Western countries highly uphold human rights. Some of the friction that occurs with the Muslim minority is a precautionary measure, not discrimination as is often presented to them. Second, the conflict between the Muslim minority and the local population is motivated by two factors (a) their ignorance of the real Islam and think that terrorist Islam is the same as King Salmanâ€™s in Saudi Arabia or ImÄm Khumaeni in Iran, and (b) improve security to protect the country and all its people from acts of terrorism. Third, discriminatory treatment occurs in the East World, China, Myanmar, Thailand, which are real examples that until now have not received a solution, even the United Nations has stated that the Rohingya are the most oppressed minority on earth.